Determination of cerium valence state in alkali and alkali-earth borates - Gaiduk, O.V.; Pantaler, R.P.; Blank, A.B. (Functional Materials, 2005)
Procedures have been elaborated for rapid, selective, and high-precise determination of Ce(IV) and total cerium content in the raw blends and single crystals of scintillators on the basis of cerium-doped alkali and rari-earth borates. Ce(IV) was determined by photometry after dissolution of the samples in sulfuric acid containing o-tolidine at room temperature. Разработаны методики, позволяющие быстро, селективно и с высокой точностью определить содержание Ce(IV) и общего церия в шихте и монокристаллах сцинтилляторов на основе боратов щелочных и редкоземельных элементов, активированных церием. Ce(IV) определяли фотометрическим методом после растворения анализируемого образца в сернокислом растворе о-толидина при комнатной температуре. Розроблено методики, що дозволяють швидко, селективно та з високою точністю визначити вміст Ce(IV) і загального церію у шихті та монокристалах сцинтиляторів на основі боратів лужних та рідкісноземельньїх елементів активованих церієм. Ce(IV) визначали фотометричним методом після розчинення зразку, що аналізується, у сірчанокислому розчині о-толідину при кімнатній температурі.